2019
DOI: 10.1007/978-3-030-33220-4_1
|View full text |Cite
|
Sign up to set email alerts
|

Usage of Semantic Web in Austrian Regional Tourism Organizations

Abstract: Tourism is one of the most important economic sectors in Austria. Given the high internationality degree of Austrian visitors, the websites of regional tourism organizations (RTOs) are an essential source of information. A state-of-the-art tourism website should include semantic markup for touristic topics so that search engines and other intelligent software applications can access and understand the presented data. This paper empirically studies the usage of Semantic Web formats, ontologies and topics releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…The results show that 57 % of examined sites used semantic markup, in which only 5 websites had marked up 85% of the semantic annotations while the usage of total annotations in each of the 32 remaining websites did not exceed 3 percent. Observed figures are similar to those found in a previous study for Austrian regions (Lohvynenko& Nedbal, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results show that 57 % of examined sites used semantic markup, in which only 5 websites had marked up 85% of the semantic annotations while the usage of total annotations in each of the 32 remaining websites did not exceed 3 percent. Observed figures are similar to those found in a previous study for Austrian regions (Lohvynenko& Nedbal, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…A previous study on 133 Austrian regional tourism organizations indicated that 59% of subjects used semantic web annotations in their web sites and the rest did not used any semantic markups. In addition, the result shows that the top 20 regions make 89% of the total amount of semantic markups (Lohvynenko& Nedbal, 2019). Smart tourism ontologies can provide big advances in tourism organization and development that worth to investigate (Navío-Marco et al, 2018).…”
Section: State Of the Artmentioning
confidence: 98%
“…L'annotation sémantique de données structurées sur un site web est l'une des pratiques d'optimisation des moteurs de recherche les plus courantes, qui est également recommandée par les principaux moteurs de recherche. Elle peut donc accroître la visibilité en ligne de la page web et les chiffres de vente sur internet (Lohvynenko & Nedbal, 2019). Les ontologies sont une composante essentielle du web sémantique pour représenter, traiter et partager les connaissances dans différents domaines.…”
Section: Introductionunclassified